Element selective oxidation on Rh–Pd bimetallic alloy surfaces. Issue 45 (7th November 2018) - Kondoh, Hiroshi; Toyoshima, Ryo; Shirahata, Naoki; Hoda, Asami; Yoshida, Masaaki; Amemiya, Kenta; Mase, Kazuhiko; Mun, Bongjin Simon
Abstract : Element selective oxidation takes place on Rh–Pd bimetallic alloy surfaces depending on the near surface initial composition. Abstract : The interactions between oxygen and Rh–Pd bimetallic alloy surfaces were investigated using surface sensitive experimental techniques and density functional theory calculations. The alloy surfaces were oxidized under 10 −5 Torr and 100 mTorr oxygen upon heating above 250 °C. A thin Rh oxide layer was preferentially formed on a Rh1 Pd9 (100) surface, while a thin Pd oxide layer was formed on a Rh1 Pd9 (111) surface, though the Rh oxide is thermodynamically more stable irrespective of the surface orientation. Chemical analyses revealed that the initial Rh fraction for the (111) surface was significantly lower than that for the (100) surface, which suggests that the oxidized element on the surface is kinetically selected depending on the near surface initial composition.